2016
DOI: 10.1007/s10584-016-1860-5
|View full text |Cite
|
Sign up to set email alerts
|

Using an option pricing approach to evaluate strategic decisions in a rapidly changing climate: Black–Scholes and climate change

Abstract: Nature provides critical ecosystem services on which society and businesses rely, but the effort and cost of utilizing those services can change with the climate. Both climatic trend and variance affect these efforts and costs, creating a complex decision space where uncertain future predictions are the rule. Here, we show how these problems mimic option payoffs and demonstrate a modified version of the Black-Scholes option pricing formula (widely used in finance) to analyze these types of business-climate dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Similar results to this study have been made in (Sturm et al, 2017) which while it examined drought, also looked at distributions at the intersection of nature and humans. (Sturm et al, 2017) demonstrated that for asymmetric human cost overlay functions on even non-lognormal natural distributions generates data that mimics options even when there is no choice, and that valuing the costs at the mean of the natural distribution gives lower values than using the entire distribution (Sturm et al, 2017). This is comparable to the methods followed for NPV flexible (Monte Carlo analysis) and NPV classic (valuing costs at the mean).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results to this study have been made in (Sturm et al, 2017) which while it examined drought, also looked at distributions at the intersection of nature and humans. (Sturm et al, 2017) demonstrated that for asymmetric human cost overlay functions on even non-lognormal natural distributions generates data that mimics options even when there is no choice, and that valuing the costs at the mean of the natural distribution gives lower values than using the entire distribution (Sturm et al, 2017). This is comparable to the methods followed for NPV flexible (Monte Carlo analysis) and NPV classic (valuing costs at the mean).…”
Section: Discussionsupporting
confidence: 83%
“…Another benefit for the decision to use log normal distributions is that the Black-Scholes option pricing formula also assumes a lognormal distribution. Sturm et al (2017) has noted that using Black-Scholes on natural systems with log normal distributions gives identical values to Monte Carlo simulations predicated on certain assumptions similar to the work as undertaken for this study. The latest regional relative SLR projections have been used as a sectoral standard reference, but these were produced in 2009 and are not up to current knowledge regarding SLR.…”
Section: Discussionmentioning
confidence: 65%
“…While not the focus of this study, these changes will have profound impacts on terrestrial and marine ecosystems and on many sectors of the Canadian economy. This includes risks related to freshwater supply from snow (Sturm et al, 2017) and other impacts of changing snow on the Canadian landscape and economy (Sturm et al, 2016). Accurately estimating dates of summer sea-icefree conditions in Canadian regions has important implications for climate studies as well as for determining impact and mitigation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a USDA Farm and Ranch Irrigation Survey [2008] found that across the Great Plains per acre foot prices varied from $7 to $65, but these turn out to be highly subsidized values. For more natural values, we [Sturm et al, 2016] water in the Valley was priced at $0.73/m 3 , or $900/acre foot. Other sources list the cost at about $250/acre foot prior to the drought, and during the drought as much as $850/acre foot (see https://www.bloomberg.com/news/ articles/2014-07-24/california-water-prices-soar-for-farmers-as-drought-grows).…”
Section: Appendix B: Computing the Cost Of Western Water Lost When Snmentioning
confidence: 99%